2022
DOI: 10.1038/s41467-022-34294-6
|View full text |Cite
|
Sign up to set email alerts
|

The first mitotic division of human embryos is highly error prone

Abstract: Human beings are made of ~50 trillion cells which arise from serial mitotic divisions of a single cell - the fertilised egg. Remarkably, the early human embryo is often chromosomally abnormal, and many are mosaic, with the karyotype differing from one cell to another. Mosaicism presumably arises from chromosome segregation errors during the early mitotic divisions, although these events have never been visualised in living human embryos. Here, we establish live cell imaging of chromosome segregation using norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 57 publications
1
39
1
Order By: Relevance
“…Extending our results to human preimplantation development suggests that lagging chromosomes are primarily responsible for mitotic errors in early embryonic cells, thus providing a mechanism for the whole-chromosome aneuploidy observed in preimplantation embryos ( Figure S5 E) ( McCoy et al., 2015 ; Starostik et al., 2020 ; Vanneste et al., 2009 ). In support, lagging chromosomes occur during the first mitotic division in human embryos ( Cavazza et al., 2021 ; Currie et al., 2022 ). In contrast, during mouse preimplantation development, unaligned chromosomes are the most frequent mitotic error ( Vázquez-Diez et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extending our results to human preimplantation development suggests that lagging chromosomes are primarily responsible for mitotic errors in early embryonic cells, thus providing a mechanism for the whole-chromosome aneuploidy observed in preimplantation embryos ( Figure S5 E) ( McCoy et al., 2015 ; Starostik et al., 2020 ; Vanneste et al., 2009 ). In support, lagging chromosomes occur during the first mitotic division in human embryos ( Cavazza et al., 2021 ; Currie et al., 2022 ). In contrast, during mouse preimplantation development, unaligned chromosomes are the most frequent mitotic error ( Vázquez-Diez et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…During mitosis, ectopic activation of the PBE pathway is more pronounced when the spindle suffers from poor anchoring (Fig 2). Since human embryos show frequent issues with spindle and chromosome capture (Kalatova et al, 2015;Cavazza et al, 2021;Currie et al, 2022), we propose that fragmentation may result from hyper-activation of the PBE pathway due to problems during chromosome separation. Importantly, ectopic activation of the PBE pathway occurs in control embryos without causing much fragmentation (Figs 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal mosaicism likely originates during the first embryonic cleavages by mitotic errors after fertilization ( 15 ), while whole aneuploidies originate from chromosome segregation errors during meiotic division for gamete formation ( 16 ). Maternal age alone may not represent the only factor associated with mosaicism; however, in the analysis of interaction and the logistic regression analysis, adjusted for all clinical characteristics, proved that age can have an isolated effect and for each 1-year increase in maternal age, the chance of low and high mosaic in relation to whole aneuploidy is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaicism occurs due to mitotic errors during the first embryonic cleavages ( 19 ). Studies have revealed that IVF laboratory conditions can increase mosaicism rates due to exposure to environmental, mechanical, and chemical stressors ( 15 , 20 , 21 ). The higher occurrence of mitoses during the blastocyst stage prompts an increased error rate.…”
Section: Discussionmentioning
confidence: 99%